Policy implications of reform in electricity supply to agriculture - Birner, Regina; Sharma, Neeru (International Food Policy Research Institute, 2011)
This chapter derives policy implications from the analysis presented in the previous chapters. The section "Reform Options" presents policy options that address the different problems associated with electricity supply to agriculture. The section "Evaluating Reform Options" assesses the political feasibility of the different options, based on the description and analysis presented in Chapters 9 and 10.